MINUMAN TRADISIONAL LOLOH DON CEMCEM SEBAGAI WELCOME DRINK DI DESA WISATA PENGLIPURAN BALI - Sinarsari, Ni Made; Sukadana, I Kadek (Paryaṭaka Jurnal Pariwisata Budaya dan Keagamaan, 2023)
The existence of a tourism destination can be known by tourists not only because of its natural beauty, but the beauty of its culture including its traditional cuisine is also one of the factors that make the area known to the public. This study aims to determine the use of the traditional drink loloh don cemcem as a welcome drink for tourists visiting the tourist village of Penglipuran, Bangli Regency - Bali. The method used is qualitative, with a field study research approach and literature study. Data collection methods used include: observation, interviews, and literature study. The results of this study indicate that Penglipuran village has been designated as a tourist village by the Bangli Regency Government since 1993 because in addition to offering a beautiful rural charm, Penglipuran village also has cultural characteristics that are different from other villages in Bali. Processing of cemcem leaves in general until they become loloh, starting from the process of preparing tools and materials. Then proceed with the process of concocting the material until it becomes loloh don cemcem until finally to the packaging process. In processing cemcem leaves to become loloh, personal hygiene is one of the important factors that should not be forgotten so that the processed loloh can provide benefits to those who consume it. Loloh don cemcem has several benefits for tourists who consume it, including: (a) relieve internal heat and increase body fluids; (b) relieve dry cough and facilitate urination; (c) promote bowel movements and maintain intestinal health (d) increase appetite; and (e) reduce hypertension. Keywords: Loloh Don Cemcem; Welcome Drinks; Penglipuran Tourism Village